Respostas morfológicas e produtivas de genótipos de Desmanthus a intervalos de corte na Zona da Mata de Pernambuco - SILVA, Leonardo Santos (2020)
Legumes belonging to the Desmanthus genus has characteristics to be used as a forage plant. The effects of cut management on Desmanthus genotype morphology and production have not been widely studied. The objective was to study the morphological and productive responses of Desmanthus spp. genotypes (7G, 31D and 13AU) under cutting intervals (60, 90, 120 and 150-days) in the Zona da Mata Norte of Pernambuco. The treatments were randomized in blocks, in a split plot scheme (genotypes in the main plots and the cutting intervals in the subplots) and four replications. The planting spacing was 0.5m x 0.5m. The evaluations took place over two years (2017 and 2018). Plant height, stem diameter, diameter of branches, length of branches, length and width of leaves, number of branches/plant and leaves/branches were measured. Also, total dry matter production (DMP), leaves, thin stems (<6mm of diameter), thick (> 6mm of diameter) and total stems, per cut and per year. The data were submitted to analysis of variance and Tukey's test at 5% of probability. The morphological and productive characteristics showed lower differences in 2018 compared to 2017. In two years, the greater leaf/stem ratio was in the 60-days interval and the plants cut at 150-days had the greater height (129 cm). The 90-days provided greater number of branches/plant (24) than 60 and 150 days, while the 120-days promoted greater leaves/branch (24) in 2017. The branches were thicker and larger, mainly in the 150-days, compared to 60-days (3 and 5 mm of diameter and 56 and 100 cm of length). The leaves were bigger and wider in the intervals of 60 and 90 days, in 2018 (about 7 and 5 cm of length and width, respectively). In 2017, the 7G genotype, despite having greater number of branches/plant (25), had smaller and narrower leaves, especially in relation to 13AU. The 13AU genotype showed greater leaf length and width (7.3 and 7.3 cm, respectively) in 2017. Regarding productivity, the 13AU genotype showed greater total DMP, with thin stems and total stems per cut and annual than the 7G in 2017 (2913, 1538 and 1957 kg DM/ha/cut and 3952, 2118 and 2538 kg DM/ha/year, for 13AU, respectively). Per cut, the total DMP was greater at 120 and 150-days (2984 and 3532 kg DM/ha/cut, respectively). However, considering the total DMP per year, both did not differ from the 90-days (average 3464 kg DM/ha/year). In 2017, more thick stems were produced in the 150-days (1051 kg DM/ha/cut) and lesser leaves (402 kg DM/ha/cut) in both years. No thick stems were observed in the 2018 period. The leaf DMP per year was greater in the 60 and 90-days in 2017 (1264 and 1138 kg DM/ha/year, respectively), while in 2018 more leaves were produced in the 60-days than in the 120 and 150-days (1134, 657 and 673 kg DM/ha/year). In general, a larger amount of thin stems was produced per cut in 60-days, compared to 150-days (557 and 1929 kg DM/ha/cut, respectively). The DMP of thin stems per year did not differ between the 60 and 150-days in 2017, but it was greater in the 150-days than in the 60-days in 2018 (2123 and 1016 kg DM/ha/year, respectively). In 60-days, both per cut and per year, lesser total stems (557 kg DM/ha/cut and 1115 kg DM/ha/year) and pods (117 kg DM/ha/cut and 233 kg DM/ha/year, respectively). It is recommended to cut genotypes of Desmanthus spp. between 60 and 90-days, aiming at greater leaf production in the biomass produced, with no thick stems. There is low morphological variability between the genotypes of Desmanthus spp. studied, however, the 7G genotype is noteworthy for developing greater number of branches in the rainy year (2017) and maintaining or increasing the leaf dimensions in the year 2018, which presented lesser rainfall. Regarding productivity, the 13AU genotype was more productive than the 7G in the rainy year, however the 7G and 31D genotypes maintained productivity between the years.